Retrospective of Providing Assistance to Children with Various Developmental Disabilities in Ukraine: 10th-20th Centuries - Yevheniia Yu. Lyndina; Oleksandr V. Kozynets (Mukachevo State University, 2021)
The study and historical and pedagogical analysis of aiding children with mental and physical disabilities make it possible to trace the development of the educational system and find ways to improve it. The purpose of the study is to investigate the issue of supporting children with various variants of developmental disorders during the 10th-20th centuries in Ukraine, analysis and justification of the problem. To fulfil this purpose, archival sources and scientific studies of scientists who studied this issue were investigated. The main chronological events of caring for children with various disorders, which later became the basis for the development of special education, are substantiated. Based on the chronicles of the Ipatiev and Lavrentiy lists, the public's awareness of the importance of raising children with hearing and speech impairments, as well as studying the elements of literacy and learning the craft, was clarified. The history of care for children with physical and intellectual disabilities in Ukraine during the 10th-20th centuries is examined. The study outlines information about the facts of the first attempts to provide pedagogical assistance in the education of the so-called "limited abilities" students in the public education system, which was preceded by the reform in the field of education. Historical data on the attitude of society towards children with various developmental disabilities in Ukraine in the period of 10th-20th centuries are analysed, as well as the dynamics of development in the field of assistance to children with mental and physical disabilities in this period. The facts about the transfer of the problem of raising children with intellectual disabilities to private institutions and the opening of psychiatric hospitals, which aided persons with developmental disabilities. The study covered I. Sikorsky's contribution to the problem of providing aid and care to those whose mental underdevelopment is a psychological and pedagogical problem. For a deeper retrospective of aiding children with various variants of developmental disabilities in Ukraine in the 10th-20th centuries, it is necessary to explore the arguments for opening and organising state assistance to various categories of children with mental and physical disabilities